2011
DOI: 10.1089/aid.2010.0320
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study of Periodontal Disease Measures and Cardiovascular Disease Markers in HIV-Infected Adults

Abstract: The determinants of HIV-associated cardiovascular disease (CVD) are not well understood. Periodontal disease (PD) has been linked to CVD but this connection has not been examined in HIV infection. We followed a cohort of HIV-infected adults to ascertain whether PD was associated with carotid artery intima media thickness (IMT) and brachial artery flow-mediated dilation (FMD). We performed a longitudinal observational study of HIVinfected adults on HAART for < 2 years with no known heart disease. PD was charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 61 publications
1
32
0
1
Order By: Relevance
“…There are several methodological limitations in earlier studies proposing a low level of PD in HIV+ adult cohorts, as detailed in our 2009 report[5]. In our 2011 longitudinal report of 43 HIV+ patients on HAART, we found that PD improved significantly during immune reconstitution on HAART[8]. We subsequently hypothesized that longitudinal improvement in CD4+ T-cell count and/or decreased level of HIV RNA would be associated with longitudinal improvement in clinical measures of PD.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…There are several methodological limitations in earlier studies proposing a low level of PD in HIV+ adult cohorts, as detailed in our 2009 report[5]. In our 2011 longitudinal report of 43 HIV+ patients on HAART, we found that PD improved significantly during immune reconstitution on HAART[8]. We subsequently hypothesized that longitudinal improvement in CD4+ T-cell count and/or decreased level of HIV RNA would be associated with longitudinal improvement in clinical measures of PD.…”
Section: Introductionmentioning
confidence: 87%
“…This was a prospective observational study of adult subjects recruited from three outpatient HIV medical clinics in Cleveland, Ohio as previously described[5,8]. IRB approval was obtained from University Hospitals Case Medical Center (UHCMC).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations